FEATURES OF GROUNDWATER USE IN VOLYN REGION - Мельнійчук, Михайло; Токарчук, Іван; Мазур, Іван (SWorldJournal, 2025)
Groundwaters, in particular mineral waters, of the Volyn region of Ukraine have been studied relatively insufficiently, which determines the low level of their use.The purpose of this study is to establish the features of the formation, distribution of u